FOMO, Insecure, dan Overthinking: Menjaga Kesehatan Mental dan Iman Remaja Muslim melalui Psikoedukasi Berbasis Masyarakat - Shafa Alistiana Irbathy; Naomi Fahma; Vebriana Intan Nur'aini; Mutiara Dahlia Nasution; Fatin Aida Dzakia (Abdimas Indonesian Journal, 2026)
The mental health of Muslim adolescents in Indonesia faces serious challenges in the digital era, with the phenomenon of Fear of Missing Out (FOMO), insecurity, and overthinking that is increasing due to social media pressure. This community service activity aims to provide psychoeducational education based on the integration of psychology and Islamic values to Muslim adolescent women in the Klaten area. The method used was a participatory approach through interactive lectures, group discussions, and practical skills training which was attended by 87 participants. The results of the activity showed an increase in participants' understanding of the three psychological phenomena, a decrease in the score of FOMO tendencies and overthinking based on pre-tests and post-tests, and an increase in participants' confidence to implement religious coping strategies such as dhikr, tawakal, and restrictions on social media consumption. This activity proves that an integrative approach that combines modern psychological insights with Islamic teachings is effective in maintaining the mental health and faith of Muslim youth in the midst of digital pressure.